SISTEM INFORMASI PEMESANAN SERAGAM SEKOLAH PADA CV. LIMA SAUDARA PALEMBANG BERBASIS WEB - Fitri Sullyanto; K. Ghazali; Suryati Suryati (UNIVERSITAS INDO GLOBAL MANDIRI)
CV. Lima Saudara is a company engaged in the manufacture of various clothing located in H Sanusi Street No..3 Lebong Siarang, Palembang. Implement system that can help the process of daily waking activities considering the activities that occur between different areas. Find schools in certain areas who like to bother in ordering uniforms because of the limitations of transfortasi tools that are not eligible school to find place of school uniforms that exist in the cities. With the online media at this time can facilitate many schools in finding distributors making school uniforms to be used for students. With the development of technology at this time will be able to help the service system in variety of products. As in ordering online care girls no longer need to come to the place of the apparel manufacturing distributor simply by opening the website provided by the distributor.This method is the Web Engineering Model, web engineering adapts the software in terms of basic concepts that emphasize technical and management activities. Online is created using UML System Design (Unified Modeling Language).This Information System aims to create website ordering school uniforms to search ordering information easier for consumers who make reservations.Keywords: Marketing, distributors, websites, web engineering method, Unified Modeling Language.